Lake Sciences and Climate Change - Rashed, M.Nageeb (IntechOpen, 2016)
Lakes are highly essential for their water quality, habitat suitability, and water supply. Lakes constitute important source for aquatic life, fish, wildlife, and human, but can undergo rapid environmental changes. Most important factors that affect lake ecosystem are climate, atmospheric inputs, land use, morphology, and physiography. Several environmental problems can affect a lake's water quality, and habitat suitability. The book "Lake Sciences and Climate Change" deals with several aspects of lake sciences (botany, zoology, geology, chemistry, models, morphology, and physiography) ,as well as the effect of climatic changes on lake body ecosystem. The book is divided into three sections and structured into 10 chapters. The first section discusses the relationship between lake and climatic change; the second section explains lake biology and health; and the third section focuses on water quality, management, and modeling. Scientists from different fields of lake sciences reported in this book their findings.